Perioperative Dysbiosis: Rethinking the Anaesthetic Contribution to Postoperative Outcomes via the Human Microbiota - Baig, Atif Amin; Thandar Htun, Aye; Myint Htoo, Phone; Hla Shwe, Wana; Zaw Win, Kyaw; Chopra, Shivani; Chopra, Hitesh (Scripta Medica, 2025)
The gut microbiome plays a crucial role in perioperative care. Surgical stress and anaesthesia disrupt the balance of intestinal flora, known as dysbiosis, which can affect gut health and metabolism. Pain relievers like morphine and certain anaesthetics contribute to this imbalance. Dysbiosis may also lead to memory loss and cognitive issues post-surgery. Future studies aim to use probiotics and beneficial substances to improve health and prevent cognitive decline.
Keywords: Dysbiosis; Microbiota; Anaesthetics; Postoperative complications